2017
DOI: 10.1002/bjs.10590
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of percutaneous tibial nerve stimulation versus sham electrical stimulation in patients with faecal incontinence

Abstract: PTNS may offer a small advantage in the clinical management of FI that is insufficiently responsive to conservative treatment. The key challenge will be to identify patients who may benefit most from this minimally invasive surgical procedure. Registration number: NCT00974909 (http://www.clinicaltrials.gov).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 29 publications
0
23
0
2
Order By: Relevance
“… 33 The benefits of PTNS for people with faecal incontinence have been questioned 34 , 35 due to the lack of pronounced clinical effects compared with a sham treatment. 36 , 37 It has been concluded that PTNS is unlikely to be recommended over SNS. 35 However, in real life, patients may prefer treatments which are less effective (although well tolerated) before considering more effective options.…”
Section: Discussionmentioning
confidence: 99%
“… 33 The benefits of PTNS for people with faecal incontinence have been questioned 34 , 35 due to the lack of pronounced clinical effects compared with a sham treatment. 36 , 37 It has been concluded that PTNS is unlikely to be recommended over SNS. 35 However, in real life, patients may prefer treatments which are less effective (although well tolerated) before considering more effective options.…”
Section: Discussionmentioning
confidence: 99%
“…In Kohortenstudien wurden die Kurzzeiterfolge mit 59-71 % beschrieben, allerdings wurden diese Ergebnisse durch eine im Jahre 2015 veröffentlichte randomisierte Multicenterstudie infrage gestellt: Das Ergebnis (mindestens 50 %ige Reduktion der Stuhlinkontinenzepisoden) nach PTNS und einer Scheinbehandlung zeigte keinen signifikanten Unterschied (38 vs. 31 %, p = 0,396) [34]. Dieses Ergebnis wurde durch eine weitere aktuelle randomisiert kontrollierte Studie bestätigt [35]. Eine Ex-post-Subanalyse der Daten dieser multizentrischen Untersuchung deutet darauf hin, dass das Verfahren möglicherweise bei Drangstuhlinkontinenz effizienter sein kann [36].…”
Section: Perkutane N-tibialis-posterior-stimulation (Ptns)unclassified
“…A systemic review, including six prospective studies of PTNS for treating FI, suggested PTNS results in significant improvements in 50-70% of patients. 8 Subsequently, two randomized controlled trials comparing PTNS with sham treatment yielded conflicting results, 9,10 although subgroup analysis in the negative trial has suggested benefit in patients with urge FI. In all of these studies, patients were required to fail conservative management, but not specifically anorectal biofeedback, before undergoing neuromodulation, and in none of the studies was PTNS evaluated in combination with BF.…”
Section: Introductionmentioning
confidence: 99%